In Vitro Metabolic Transformation of Pharmaceuticals by Hepatic S9 Fractions from Common Carp (Cyprinus carpio) - Burkina, Viktoriia; Sakalli, Sidika; Giang, Pham Thai; Grabicová, Kateřina; Staňová, Andrea Vojs; Zamaratskaia, Galia; Zlabek, Vladimir (Molecules (Basel, Switzerland), 2020)
Water from wastewater treatment plants contains concentrations of pharmaceutically active compounds as high as micrograms per liter, which can adversely affect fish health and behavior, and contaminate the food chain. Here, we tested the ability of the common carp hepatic S9 fraction to produce the main metabolites from citalopram, metoprolol, sertraline, and venlafaxine. Metabolism in fish S9 fractions was compared to that in sheep. The metabolism of citalopram was further studied in fish. Our results suggest a large difference in the rate of metabolites formation between fish and sheep. Fish hepatic S9 fractions do not show an ability to form metabolites from venlafaxine, which was also the case for sheep. Citalopram, metoprolol, and sertraline were metabolized by both fish and sheep S9. Citalopram showed concentration-dependent N-desmethylcitalopram formation with Vmax = 1781 pmol/min/mg and Km = 29.7 μM. The presence of ellipticine, a specific CYP1A inhibitor, in the incubations reduced the formation of N-desmethylcitalopram by 30-100% depending on the applied concentration. These findings suggest that CYP1A is the major enzyme contributing to the formation of N-desmethylcitalopram. In summary, the results from the present in vitro study suggest that common carp can form the major metabolites of citalopram, metoprolol, and sertraline.
Keywords: Sertraline; Carps; metabolite formation; Cytochrome P-450 CYP1A1; Venlafaxine Hydrochloride; venlafaxine; Female; In Vitro Techniques; Citalopram; sertralin; cytochrom P-450 CYP1A1; techniky in vitro; léčivé přípravky; sertraline; Microsomes, Liver; cytochrome P450; environmental toxicology; Sheep; Metoprolol; mužské pohlaví; jaterní mikrozomy; zvířata; metoprolol; kapři; ženské pohlaví; Animals; citalopram; Male; ovce; Pharmaceutical Preparations; venlafaxin hydrochlorid